Implementasi Media Game Edukasi Wordwall untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN Mojoroto 4 Kota Kediri - Kurnia, Nila; Permana, Erwin Putera; Permatasari, Cecilia (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to improve student learning outcomes through wordwall educational game media for fourth grade students at SDN Mojoroto 4. This research was conducted at SDN Mojoroto 4. The type of research used was Classroom Action Research (CAR) using the Kurt Lewin model. The data collection instruments used were observation, tests, and documentation. The results of this study were that in cycle I, the percentage of complete learning outcomes was obtained by 63% or 15 students who had completed their studies while 37% or 9 students had not completed their studies. The results of cycle II showed that the percentage of completeness of student learning outcomes was 83% or 20 students had completed their studies while 17% or 4 students had not completed their studies. This is an increase of 20% of students who meet the criteria of completion in learning. There is a significant increase in learning outcomes with wordwall educational game media for fourth grade students at SDN Mojoroto 4.